ANALISIS MISKONSEPSI SISWA KELAS V DALAM PEMBELAJARAN IPAS DAN STRATEGI REMEDIASI BERBASIS INKUIRI TERBIMBING - Effiana Cahya Ningrum; Lailatul I’zaati; Apriliyanti Muzayanati; Ayu Zafira Ramadhani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Misconceptions in ecosystem topics represent a serious barrier in IPAS learning that negatively impacts student achievement. This study aims to identify misconceptions among fifth-grade students at MI Al-Islam Madugondo, analyze their contributing factors, and examine the effectiveness of guided inquiry-based remediation. A descriptive qualitative approach was employed, with data collected through diagnostic tests, interviews, observations, and documentation, and analyzed using the Miles and Huberman model. The findings reveal five major misconceptions: misunderstanding of food chain flow, the role of decomposers, the concept of symbiosis, biotic-abiotic component relationships, and ecosystem balance. Contributing factors include prior misconceived knowledge, limited real-world experience, and insufficiently contextual teaching methods. Following remediation through the stages of orientation, exploration, discussion, and reflection, students demonstrated significant shifts in understanding toward scientifically accurate concepts. Guided inquiry proved to be an effective remediation strategy for addressing ecosystem misconceptions at the MI level.